Short fluorocarbon chain-based amphiphobic coating and preparation method and application thereof

By using the synergistic effect of solidifying promoters and binders and silica compounds in the preparation of shortfluorocarbon chain substances, the problem of complex and stability of the short fluorocarbon chain dual sparse coating process is solved, and stable hydrophobic oil is achieved. Preparation of pollution -proof textiles.

CN116516694BActive Publication Date: 2025-01-28TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310567010.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-19
Publication Date
2025-01-28
Estimated Expiration
2043-05-19

AI Technical Summary

Technical Problem

In the prior art, the preparation process of short fluorocarbon chain double-sparse coatings is complex, and the prepared double-sparse films have poor stability, making it difficult to find a balance between environmental friendliness and stability.

Method used

Use a curing promoter to uniformly dissolved the short fluorocarbon chain substance in the first organic solvent, prepare solid powder -like fluorine -containing substances, and synergistic effects through the binder in the second organic solvent to the synergy of the binder in the second organic solvent. The fluorine -containing material is stable to the surface of the fabric fiber, and water -sparse, oil -sparse, and pollution -proof textile fabrics are constructed.

Benefits of technology

The stable preparation of short fluorocarbon chain -based double sparse coatings has been realized. The prepared hydrophobic oil -proof textile -proof textiles have good stability and pollution -proof performance, and can still maintain a good hydrophobic oil and oil and oil effect after 1 month.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116516694B_ABST
    Figure CN116516694B_ABST
Patent Text Reader

Abstract

The invention discloses a short fluorocarbon chain-based amphiphobic coating, a preparation method and application thereof. The preparation method of the short fluorocarbon chain-based amphiphobic coating comprises the following steps: uniformly dispersing a curing accelerator in a first organic solvent, adding a short fluorocarbon chain substance, stirring, and drying to obtain a solid powder fluorine-containing substance; uniformly dispersing the solid powder fluorine-containing substance in a second organic solvent, adding inorganic nanoparticles, stirring evenly, adding a silane compound and a binder, stirring evenly at room temperature to obtain the short fluorocarbon chain-based amphiphobic coating. The hydrophobic and oleophobic antifouling textiles prepared by the short fluorocarbon chain-based amphiphobic coating of the invention can achieve hydrophobic and oleophobic effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of amphiphobic coatings, and in particular relates to a short fluorocarbon chain-based amphiphobic coating and a preparation method and application thereof. Background Art

[0002] Textiles are considered to be a flexible, comfortable, low-cost and biodegradable environmentally friendly material, and are widely chosen as the main clothing material in daily life. Most textiles are porous and breathable, and due to the rich presence of hydroxyl groups on their surfaces, they can quickly absorb water, oil and some polluting liquids. Contaminated textiles need to be washed many times, increasing daily water and electricity consumption and sewage discharge. Therefore, the development of textile fabrics with anti-fouling properties such as waterproof and oil-proof has attracted great attention in the industry.

[0003] The contact angle of water droplets on the surface of the material is greater than 90°, which is generally called a hydrophobic material. In particular, the contact angle of water droplets on the surface of the material is greater than 150°, which is generally called a super-hydrophobic material. Similarly, the contact angle of oil droplets on the surface of the material is greater than 90°, which is called an oleophobic material, and the contact angle of oil droplets on the surface of the material is greater than 150°, which is called a super-oleophobic material. In nature, water droplets on the surface of lotus leaves can gather into a sphere and roll down, taking away sludge while also having good self-cleaning properties. Through in-depth research on animals and plants that can produce super-hydrophobicity in nature, great progress has been made in the preparation of super-hydrophobic coatings. However, the research and preparation of super-oleophobic coatings are relatively small. Because the preparation of super-oleophobic coatings is much more complicated than the preparation of super-hydrophobic coatings. Current studies have shown that the composite of long fluorocarbon chain substances (fluorocarbon number Nc>8) with very low surface energy and rough structures can achieve surface oleophobicity, so that the surface of the material presents hydrophobic-oleophobic dual functional characteristics. In view of the excellent low surface energy and chemical stability of long fluorocarbon chain substances, they are very effective in oil prevention and decontamination. Therefore, the currently reported double-repellent coatings generally use long fluorocarbon chain substances as low surface energy substances to modify substrates such as fabrics, glass, and metals, such as perfluorodecyl trichlorosilane (CN 115323352 A, published on November 11, 2022), perfluorodecyl trimethoxysilane (CN 114276704 A, published on April 15, 2022), 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane (CN 115506160 A, published on December 23, 2022), etc. However, due to the high toxicity and bioaccumulation of the degradation products of long fluorocarbon chain substances, it has been banned from use in textiles and requires zero emissions. Nowadays, the academic community is interested in the development of the use of short fluorocarbon chain substances (fluorocarbon chain length Nc≤6) because short fluorocarbon chain substances are less prone to bioaccumulation. In order to make the short fluorocarbon chain substance give fabric hydrophobicity and oleophobicity, the current reporting method generally mixes the short fluorocarbon chain substance and alkyl acrylate substances in a solvent, and the copolymerization reaction is initiated by an initiator in an oxygen-free environment to obtain a double sparse coating. Such as homemade short fluorocarbon chain substances and methyl acrylate are mixed in tetrahydrofuran solvent, copolymerization reaction (CN 113322680 A) is initiated by azobisisobutyronitrile, homemade short fluorocarbon chain substances and vinyl acetate are mixed in an aqueous solvent, and copolymerization reaction (CN 107602754 A) is initiated by potassium persulfate in an oxygen-free environment. But the preparation process of these double sparse coatings is complex, and the stability of the prepared double sparse film is poor. Therefore, the development of environmentally friendly, stable short fluorocarbon chain double sparse coatings is still a difficulty in the prior art. Summary of the invention

[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for preparing a short fluorocarbon chain-based double-repellent coating, which uses a curing accelerator to uniformly dissolve a short fluorocarbon chain substance in a first organic solvent to prepare a solid powdered fluorine-containing substance, and uses a binder and a silane compound in a second organic solvent to stably attach inorganic nanoparticles and a fluorine-containing substance with low surface properties (solid powdered fluorine-containing substance) to the surface of fabric fibers, thereby constructing a hydrophobic (deionized water, surface tension of 72.0 mN / m), oleophobic (soybean oil, surface tension of 33.0 mN / m), and anti-fouling textile.

[0005] Another object of the present invention is to provide a short fluorocarbon chain-based amphiphobic coating obtained by the above preparation method.

[0006] Another object of the present invention is to provide the use of short fluorocarbon chain-based amphiphobic coatings in hydrophobicity and / or oleophobicity.

[0007] The purpose of the present invention is achieved through the following technical solutions.

[0008] A method for preparing a short fluorocarbon chain-based amphiphobic coating comprises the following steps:

[0009] 1) uniformly dispersing a curing accelerator in a first organic solvent, adding a short fluorocarbon chain substance, stirring at 30 to 80° C. for 2 to 10 hours, and drying to obtain a solid powder fluorine-containing substance;

[0010] In the step 1), the ratio of the first organic solvent, the curing accelerator and the short fluorocarbon chain substance is 100:(10-15):(4-10) by volume.

[0011] In the step 1), the curing accelerator is a mixture of one or more of ethylenediamine, triethylamine and methylamine.

[0012] In the step 1), the short fluorocarbon chain substance is a fluorocarbon compound with a chain length of 4 to 6.

[0013] In the above technical solution, the short fluorocarbon chain substance is perfluorohexylsulfonyl fluoride or perfluorobutylsulfonyl fluoride.

[0014] In the step 1), the drying temperature is 100-150°C.

[0015] In the step 1), the drying is vacuum drying.

[0016] In the step 1), the short fluorocarbon chain substance is in liquid state.

[0017] In the step 1), the first organic solvent is n-hexane or tetrahydrofuran.

[0018] 2) Dispersing the solid powder fluorine-containing substance uniformly in a second organic solvent, adding inorganic nanoparticles, stirring uniformly, adding a silane compound and a binder, stirring uniformly at room temperature, and obtaining a short fluorocarbon chain-based amphiphilic coating, wherein the ratio of the mass fraction of the solid powder fluorine-containing substance, the mass fraction of the inorganic nanoparticles, the volume fraction of the silane compound, and the volume fraction of the binder is (0.5-2): (0.2-0.8): (10-30): (0.5-2).

[0019] In the step 2), the unit of the mass fraction is g, and the unit of the volume fraction is mL.

[0020] In the step 2), the ratio of the second organic solvent to the silane compound is 100:(10-30) by volume.

[0021] In the step 2), the inorganic nanoparticles are one or a mixture of zinc oxide, silicon dioxide and titanium dioxide.

[0022] In the step 2), the second organic solvent is an alcohol solvent, such as ethanol or methanol.

[0023] In the step 2), the silane compound is hexadecyltrimethoxysilane or dodecyltrimethoxysilane.

[0024] In the step 2), the adhesive is epoxy resin or fluorocarbon resin.

[0025] The short fluorocarbon chain-based amphiphobic coating obtained by the above preparation method.

[0026] Application of the above short fluorocarbon chain-based amphiphobic coating in hydrophobicity and / or oleophobicity.

[0027] In the above technical solution, the short fluorocarbon chain-based amphiphobic coating is dip-coated or sprayed onto the surface of the textile and dried to obtain the hydrophobic, oleophobic and antifouling textile.

[0028] In the above technical solution, the textile is a chemical fiber textile, a cotton textile or a linen textile.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The preparation method of the present invention prepares a fluorine-containing substance (solid powder fluorine-containing substance) from a short fluorine-carbon chain substance under the action of a curing accelerator, and dissolves the fluorine-containing substance, a silane compound, inorganic nanoparticles and a binder in a second organic solvent. In the preparation method, the short fluorine-carbon chain substance can participate in the generation process of the amphiphobic particles on the one hand; on the other hand, it can participate in the curing film-forming process of coating on the surface of the textile (fiber material) to construct a stable amphiphobic film.

[0031] (2) The short fluorocarbon chain-based amphiphobic coating of the present invention has good stability and can be placed for 1 month and still be used.

[0032] (3) The hydrophobic and oleophobic antifouling textiles prepared by the short fluorocarbon chain-based dual-repellent coating of the present invention can achieve hydrophobic and oleophobic effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is the surface water drop contact angle of the hydrophobic and oleophobic antifouling textile in Example 1;

[0034] Figure 2 is the surface oil drop contact angle of the hydrophobic and oleophobic antifouling textile in Example 1;

[0035] Figure 3 is the surface water drop contact angle of the hydrophobic and oleophobic antifouling textile in Example 1;

[0036] Figure 4 is the surface oil drop contact angle of the hydrophobic and oleophobic antifouling textile in Example 1;

[0037] Figure 5 is the surface water drop contact angle of the hydrophobic and oleophobic antifouling textile in Example 2;

[0038] Figure 6 is the surface oil drop contact angle of the hydrophobic and oleophobic antifouling textile in Example 2;

[0039] Figure 7 is the surface water drop contact angle of the hydrophobic and oleophobic antifouling textile in Example 3;

[0040] Figure 8 is the surface oil drop contact angle of the hydrophobic and oleophobic antifouling textile in Example 3;

[0041] Fig. 9 is the surface water drop contact angle of the hydrophobic and oleophobic antifouling textile in Example 4;

[0042] Fig.10 is the surface oil drop contact angle of the hydrophobic and oleophobic antifouling textile in Example 4;

[0043] Fig.11 The surface water drop contact angle of the coated textile obtained in Comparative Example 1;

[0044] Fig.12 This is the surface oil drop contact angle of the coated textile obtained in Comparative Example 1. DETAILED DESCRIPTION

[0045] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0046] The drugs involved in the following embodiments are as follows:

[0047] Hexane: 99%, Shanghai McLean Biochemical Technology Co., Ltd. Tetrahydrofuran: 99%, Shanghai McLean Biochemical Technology Co., Ltd. Perfluorobutylsulfonyl fluoride: 96%, Shanghai McLean Biochemical Technology Co., Ltd. Perfluorohexylsulfonyl fluoride: 97%, Shanghai McLean Biochemical Technology Co., Ltd. Ethylenediamine: 99%, Shanghai McLean Biochemical Technology Co., Ltd.

[0048] Triethylamine: 99%, Shanghai McLean Biochemical Technology Co., Ltd. Methylamine: 98%, Shanghai McLean Biochemical Technology Co., Ltd. Hexadecyltrimethoxysilane: 85%, Shanghai McLean Biochemical Technology Co., Ltd. Dodecyltrimethoxysilane: 95%, Shanghai McLean Biochemical Technology Co., Ltd. Methanol: 99.5%, Shanghai McLean Biochemical Technology Co., Ltd. Ethanol: 99.7%, Shanghai McLean Biochemical Technology Co., Ltd. Nano silicon dioxide, average particle size 30nm, Shanghai McLean Biochemical Technology Co., Ltd. Nano titanium dioxide, average particle size 60nm, Shanghai McLean Biochemical Technology Co., Ltd. Nano zinc oxide, average particle size 90nm, Shanghai McLean Biochemical Technology Co., Ltd.

[0049] Epoxy resin, Model: 150T, Shenzhen Aosbon Co., Ltd.

[0050] Fluorocarbon resin, Model: DuPont FS-30, DuPont (China) Co., Ltd. Shanghai Branch

[0051] Polyester fiber fabric, cotton fiber fabric and linen fiber fabric were purchased from Tianjin Huada Garment Co., Ltd.

[0052] Example 1

[0053] A method for preparing a short fluorocarbon chain-based amphiphobic coating comprises the following steps:

[0054] 1) The curing accelerator is uniformly dispersed in the first organic solvent, and the liquid short fluorocarbon chain substance is added, stirred evenly, stirred at 30° C. for 3 hours, and vacuum dried at 100° C. for 2 days to obtain a solid powder fluorine-containing substance, wherein the curing accelerator is ethylenediamine, the short fluorocarbon chain substance is perfluorobutylsulfonyl fluoride, and the first organic solvent is n-hexane. The ratio of the first organic solvent, the curing accelerator and the short fluorocarbon chain substance is 100:12:6 by volume.

[0055] 2) The solid powder fluorine-containing substance is uniformly dispersed in the second organic solvent, and then inorganic nanoparticles are added, stirred evenly, and silane compounds and binders are added, and stirred evenly at room temperature to obtain a short fluorocarbon chain-based double-repellent coating, wherein the mass fraction of the solid powder fluorine-containing substance, the mass fraction of the inorganic nanoparticles, the volume fraction of the silane compound and the volume fraction of the binder are 0.5:0.2:10:0.5, the unit of mass fraction is g, the unit of volume fraction is mL, and the ratio of the second organic solvent to the silane compound is 100:10 by volume fraction. The inorganic nanoparticles are nano-silicon dioxide, and the second organic solvent is ethanol. The silane compound is hexadecyltrimethoxysilane, and the binder is epoxy resin.

[0056] The short fluorocarbon chain-based amphiphobic coating obtained in this example is applied to textiles: the textiles are immersed in the short fluorocarbon chain-based amphiphobic coating for 30 minutes, the short fluorocarbon chain-based amphiphobic coating is applied to the surface of the textiles, and dried at 80°C for 2 hours to obtain hydrophobic, oleophobic and antifouling textiles, wherein the textiles are polyester fiber fabrics (chemical fiber textiles) washed with ethanol and deionized water.

[0057] The DSA100 contact angle tester was used to test the water drop contact angle and oil drop contact angle (soybean oil) of hydrophobic and oleophobic antifouling textiles. The results are as follows Figure 1 , Figure 2 As shown, the water drop contact angle of the obtained hydrophobic and oleophobic antifouling textile is 149.6°, and the oil drop contact angle is 137.9°, showing hydrophobic and oleophobic properties.

[0058] The obtained hydrophobic and oleophobic antifouling textile was placed for 1 month and then the water drop contact angle and oil drop contact angle were tested. Figure 3 , Figure 4 As shown, the water drop contact angle of the obtained hydrophobic and oleophobic antifouling textile is 149.2°, and the oil drop contact angle is 137.6°. It can be seen that after one month of storage, the change of the water drop contact angle and the oil drop contact angle on the surface of the obtained material is less than 0.5°, showing a relatively stable hydrophobic and oleophobic performance.

[0059] Example 2

[0060] A method for preparing a short fluorocarbon chain-based amphiphobic coating comprises the following steps:

[0061] 1) The curing accelerator is uniformly dispersed in the first organic solvent, and the liquid short fluorocarbon chain substance is added, stirred evenly, stirred at 70° C. for 8 hours, and vacuum dried at 140° C. for 2 days to obtain a solid powder fluorine-containing substance, wherein the curing accelerator is triethylamine, the short fluorocarbon chain substance is perfluorohexylsulfonyl fluoride, and the first organic solvent is n-hexane. The ratio of the first organic solvent, the curing accelerator and the short fluorocarbon chain substance is 100:14:6 by volume.

[0062] 2) The solid powder fluorine-containing substance is uniformly dispersed in the second organic solvent, and then inorganic nanoparticles are added, stirred evenly, and silane compounds and binders are added, and stirred evenly at room temperature to obtain a short fluorocarbon chain-based double-repellent coating, wherein the ratio of the mass fraction of the solid powder fluorine-containing substance, the mass fraction of the inorganic nanoparticles, the volume fraction of the silane compound and the volume fraction of the binder is 1.8:0.5:30:1.5, the unit of mass fraction is g, the unit of volume fraction is mL, and the ratio of the second organic solvent to the silane compound is 100:30 by volume fraction. The inorganic nanoparticles are nano-silicon dioxide, and the second organic solvent is methanol. The silane compound is dodecyltrimethoxysilane, and the binder is a fluorocarbon resin.

[0063] The short fluorocarbon chain-based amphiphobic coating obtained in this example is applied to textiles: the textiles are immersed in the short fluorocarbon chain-based amphiphobic coating for 50 minutes, the short fluorocarbon chain-based amphiphobic coating is applied to the surface of the textiles, and the textiles are dried at 100°C for 10 hours to obtain hydrophobic, oleophobic and antifouling textiles, wherein the textiles are polyester fiber fabrics (chemical fiber textiles) washed with ethanol and deionized water.

[0064] The DSA100 contact angle tester was used to test the water drop contact angle and oil drop contact angle (soybean oil) of hydrophobic and oleophobic antifouling textiles. The results are as follows Figure 5 , Figure 6 As shown, the water drop contact angle of the obtained hydrophobic and oleophobic antifouling textile is 146.4°, and the oil drop contact angle is 135.5°, showing hydrophobic and oleophobic properties.

[0065] Example 3

[0066] A method for preparing a short fluorocarbon chain-based amphiphobic coating comprises the following steps:

[0067] 1) The curing accelerator is uniformly dispersed in the first organic solvent, and the liquid short fluorocarbon chain substance is added, stirred evenly, stirred at 80° C. for 6 hours, and vacuum dried at 130° C. for 4 days to obtain a solid powder fluorine-containing substance, wherein the curing accelerator is triethylamine, the short fluorocarbon chain substance is perfluorohexylsulfonyl fluoride, and the first organic solvent is tetrahydrofuran. The ratio of the first organic solvent, the curing accelerator and the short fluorocarbon chain substance is 100:15:8 by volume.

[0068] 2) The solid powder fluorine-containing substance is uniformly dispersed in the second organic solvent, and then inorganic nanoparticles are added, stirred evenly, and silane compounds and binders are added, and stirred evenly at room temperature to obtain a short fluorocarbon chain-based double-repellent coating, wherein the mass fraction of the solid powder fluorine-containing substance, the mass fraction of the inorganic nanoparticles, the volume fraction of the silane compound and the volume fraction of the binder are 1.5:0.6:20:0.5, the unit of mass fraction is g, the unit of volume fraction is mL, and the ratio of the second organic solvent to the silane compound is 100:20 by volume fraction. The inorganic nanoparticles are nano zinc oxide, and the second organic solvent is methanol. The silane compound is dodecyltrimethoxysilane, and the binder is a fluorocarbon resin.

[0069] The short fluorocarbon chain-based amphiphobic coating obtained in this example is applied to textiles: the textiles are immersed in the short fluorocarbon chain-based amphiphobic coating for 40 minutes, the short fluorocarbon chain-based amphiphobic coating is dip-coated onto the surface of the textiles, and dried at 100°C for 4 hours to obtain hydrophobic, oleophobic and antifouling textiles, wherein the textiles are cotton fiber fabrics washed with ethanol and deionized water (purchased from Tianjin Huada Garment Co., Ltd.).

[0070] The DSA100 contact angle tester was used to test the water drop contact angle and oil drop contact angle (soybean oil) of hydrophobic and oleophobic antifouling textiles. The results are as follows Figure 7 , Figure 8 As shown, the water drop contact angle of the obtained hydrophobic and oleophobic antifouling textile is 142.6°, and the oil drop contact angle is 134.1°, showing hydrophobic and oleophobic properties.

[0071] Example 4

[0072] A method for preparing a short fluorocarbon chain-based amphiphobic coating comprises the following steps:

[0073] 1) The curing accelerator is uniformly dispersed in the first organic solvent, and the liquid short fluorocarbon chain substance is added, stirred evenly, stirred at 50° C. for 4 hours, and vacuum dried at 120° C. for 4 days to obtain a solid powder fluorine-containing substance, wherein the curing accelerator is methylamine, the short fluorocarbon chain substance is perfluorobutylsulfonyl fluoride, and the first organic solvent is tetrahydrofuran. The ratio of the first organic solvent, the curing accelerator and the short fluorocarbon chain substance is 100:11:9 by volume.

[0074] 2) The solid powder fluorine-containing substance is uniformly dispersed in the second organic solvent, and then inorganic nanoparticles are added, stirred evenly, and silane compounds and binders are added, and stirred evenly at room temperature to obtain a short fluorocarbon chain-based double-repellent coating, wherein the ratio of the mass fraction of the solid powder fluorine-containing substance, the mass fraction of the inorganic nanoparticles, the volume fraction of the silane compound and the volume fraction of the binder is 2:0.8:15:1, the unit of mass fraction is g, the unit of volume fraction is mL, and the ratio of the second organic solvent to the silane compound is 100:15 by volume fraction. The inorganic nanoparticles are nano titanium dioxide, and the second organic solvent is ethanol. The silane compound is dodecyltrimethoxysilane, and the binder is epoxy resin.

[0075] The short fluorocarbon chain-based amphiphobic coating obtained in this example is applied to textiles: the textiles are immersed in the short fluorocarbon chain-based amphiphobic coating for 60 minutes, the short fluorocarbon chain-based amphiphobic coating is dip-coated onto the surface of the textiles, and dried at 90°C for 8 hours to obtain hydrophobic, oleophobic and antifouling textiles, wherein the textiles are hemp fiber fabrics washed with ethanol and deionized water (purchased from Tianjin Huada Garment Co., Ltd.).

[0076] The DSA100 contact angle tester was used to test the water drop contact angle and oil drop contact angle (soybean oil) of hydrophobic and oleophobic antifouling textiles. The results are as follows Fig. 9 , Fig.10 As shown, the water drop contact angle of the obtained hydrophobic and oleophobic antifouling textile is 143.7°, and the oil drop contact angle is 131.1°, showing hydrophobic and oleophobic properties.

[0077] Comparative Example 1

[0078] A method for preparing a coating comprises the following steps:

[0079] 1) Evenly dispersing a liquid short fluorocarbon chain substance in a first organic solvent to obtain a liquid B, wherein the short fluorocarbon chain substance is perfluorobutylsulfonyl fluoride, the first organic solvent is n-hexane, and the ratio of the first organic solvent to the short fluorocarbon chain substance is 100:6 by volume.

[0080] 2) Liquid B is evenly dispersed in a second organic solvent, and then inorganic nanoparticles are added, stirred evenly, and a silane compound and a binder are added, and stirred evenly at room temperature to obtain a coating, wherein the ratio of the volume fraction of liquid B, the mass fraction of inorganic nanoparticles, the volume fraction of the silane compound, and the volume fraction of the binder is 0.5:0.2:10:0.5, the unit of mass fraction is g, the unit of volume fraction is mL, and the ratio of the second organic solvent to the silane compound is 100:10 by volume fraction. The inorganic nanoparticles are nano-silicon dioxide, and the second organic solvent is ethanol. The silane compound is hexadecyltrimethoxysilane, and the binder is epoxy resin.

[0081] The coating obtained in this comparative example is applied to textiles: the textiles are immersed in the coating for 30 minutes, the coating is applied to the surface of the textiles, and the textiles are dried at 80° C. for 2 hours to obtain coated textiles, wherein the textiles are polyester fiber fabrics (chemical fiber textiles) washed with ethanol and deionized water.

[0082] The DSA100 contact angle tester was used to test the water drop contact angle and oil drop contact angle (soybean oil) of the coated textiles. The results are as follows Fig.11 , Fig.12 As shown, the water droplet contact angle of the obtained coated textile is 116.8°, and the oil droplet contact angle is 0°, showing hydrophobicity but no oleophobicity.

[0083] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing a short fluorocarbon chain-based amphiphilic coating, characterized in that: The following steps are involved: 1) uniformly dispersing a curing accelerator in a first organic solvent, adding a short fluorocarbon chain substance, stirring at 30 to 80° C. for 2 to 10 hours, and drying to obtain a solid powder fluorine-containing substance; 2) Dispersing the solid powder fluorine-containing substance uniformly in a second organic solvent, adding inorganic nanoparticles, stirring uniformly, adding a silane compound and a binder, stirring uniformly at room temperature, and obtaining a short fluorocarbon chain-based amphiphilic coating, wherein the ratio of the mass fraction of the solid powder fluorine-containing substance, the mass fraction of the inorganic nanoparticles, the volume fraction of the silane compound, and the volume fraction of the binder is (0.5-2): (0.2-0.8): (10-30): (0.5-2), the unit of the mass fraction is g, and the unit of the volume fraction is mL.

2. The preparation method according to claim 1, characterized in that: In the step 1), the curing accelerator is a mixture of one or more of ethylenediamine, triethylamine and methylamine; the short fluorocarbon chain substance is a fluorocarbon compound with a chain length of 4 to 6, and the ratio of the first organic solvent, the curing accelerator and the short fluorocarbon chain substance is 100: (10 to 15): (4 to 10) by volume.

3. The preparation method according to claim 1, characterized in that: The first organic solvent is n-hexane or tetrahydrofuran, the second organic solvent is ethanol or methanol, and the inorganic nanoparticles are one or a mixture of zinc oxide, silicon dioxide and titanium dioxide.

4. The preparation method according to claim 1, characterized in that: In the step 1), the binder is epoxy resin or fluorocarbon resin, and the silane compound is hexadecyltrimethoxysilane or dodecyltrimethoxysilane.

5. The preparation method according to claim 1, characterized in that: The short fluorocarbon chain substance is perfluorohexylsulfonyl fluoride or perfluorobutylsulfonyl fluoride.

6. The preparation method according to claim 1, characterized in that: In terms of volume fractions, the ratio of the second organic solvent to the silane compound is 100:(10-30).

7. The preparation method according to claim 1, characterized in that: In the step 1), the drying temperature is 100-150° C., and the drying is vacuum drying.

8. The short fluorocarbon chain-based amphiphobic coating obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the short fluorocarbon chain-based amphiphobic coating as claimed in claim 8 in hydrophobicity and / or oleophobicity.

10. The use according to claim 9, characterized in that: The short fluorocarbon chain-based amphiphobic coating is dip-coated or sprayed onto the surface of the textile and dried to obtain the hydrophobic, oleophobic and antifouling textile.

Citation Information

Patent Citations

  • Preparation method of polymer containing short fluorocarbon chain, and preparation method of polymer

    CN107602754A

  • Short-fluorine-chain fabric finishing agent as well as preparation method and application thereof

    CN113322680A

  • Super-amphiphobic coating as well as preparation method and application thereof

    CN114276704A

  • Super-amphiphobic coating with micro-nano composite structure and preparation method of super-amphiphobic coating

    CN115323352A

  • Water-based amphiphobic coating as well as preparation method and application thereof

    CN115506160A